2018
DOI: 10.1073/pnas.1717069115
|View full text |Cite
|
Sign up to set email alerts
|

Light color acclimation is a key process in the global ocean distribution ofSynechococcus cyanobacteria

Abstract: Marine cyanobacteria are major contributors to global oceanic primary production and exhibit a unique diversity of photosynthetic pigments, allowing them to exploit a wide range of light niches. However, the relationship between pigment content and niche partitioning has remained largely undetermined due to the lack of a single-genetic marker resolving all pigment types (PTs). Here, we developed and employed a robust method based on three distinct marker genes (, , and) to estimate the relative abundance of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
165
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(179 citation statements)
references
References 63 publications
12
165
2
Order By: Relevance
“…As predicted, these two genera coexist in many regions across the global ocean but their distributions do not completely overlap (Ting et al 2002, Flombaum et al 2013. In agreement with the model predictions, Prochlorococcus uses chlorophyllbased light-harvesting antennae and is particularly abundant in blue waters of the oligotrophic subtropical gyres (Partensky et al 1999, Biller et al 2015, whereas the PBS-containing Synechococcus prevails in slightly more turbid oceanic and coastal waters dominated by greenish blue and green light (Scanlan and West 2002, Ting et al 2002, Gr ebert et al 2018. Moreover, the highly diverse Synechococcus genus comprises several pigment types, that have branched out over a wide range of aquatic ecosystems in accordance with the underwater light colors that can be captured by their phycobili-pigments (Stomp et al 2007, Gr ebert et al 2018).…”
Section: Implications For Natural Phytoplankton Communitiessupporting
confidence: 81%
“…As predicted, these two genera coexist in many regions across the global ocean but their distributions do not completely overlap (Ting et al 2002, Flombaum et al 2013. In agreement with the model predictions, Prochlorococcus uses chlorophyllbased light-harvesting antennae and is particularly abundant in blue waters of the oligotrophic subtropical gyres (Partensky et al 1999, Biller et al 2015, whereas the PBS-containing Synechococcus prevails in slightly more turbid oceanic and coastal waters dominated by greenish blue and green light (Scanlan and West 2002, Ting et al 2002, Gr ebert et al 2018. Moreover, the highly diverse Synechococcus genus comprises several pigment types, that have branched out over a wide range of aquatic ecosystems in accordance with the underwater light colors that can be captured by their phycobili-pigments (Stomp et al 2007, Gr ebert et al 2018).…”
Section: Implications For Natural Phytoplankton Communitiessupporting
confidence: 81%
“…The same study shed light on the flexible genome of marine picocyanobacteria, showing genomic islands and hypervariable regions containing genes involved in LPS synthesis, ABC transporters, transcriptional regulators, DNA mobility or phage defence systems (Dufresne et al ., ). One of these islands contains the genes for PBS synthesis and regulation, a feature that allows Synechococcus to adapt to different light conditions, with some strains being chromatic adaptors (Six et al ., ) that are ecologically abundant (Grébert et al ., ). Distribution patterns of different marine Synechococcus ecotypes revealed open ocean, coastal and opportunistic specialists (Dufresne et al ., ; Zwirglmaier et al ., ; Sohm et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In the oceans, microdiverse Synechococcus lineages inhabit different regions of the globe across large spatial scales (Zwirglmaier et al, 2008;Farrant et al, 2016), allowing this genus to occupy virtually all ocean waters. One important picocyanobacterial phenotypic characteristic is their accessory pigment composition (presence of various combinations of phycoerythrin and phycocyanin in their phycobilisomes, hereafter PBS), which makes them efficient light harvesters, photosynthesizing at different depths and across a range of light intensities (Vörös et al, 1998;Stomp et al, 2007;Grébert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pro and Syn are both ecologically dominant and widespread members in warm oligotrophic waters (Liu et al 2007, Seymour et al 2010, although Pro are gen-erally more abundant than Syn and PEuks, often by 10-fold or more in the open ocean (Jiao & Yang 2002, Flombaum et al 2013. Furthermore, Syn and PEuks have a wide geographical distribution that covers both oligo-and mesotrophic oceanic and coastal areas from pole to pole (Olson et al 1990, Flombaum et al 2013, Grébert et al 2018. Observations in the oligotrophic Pacific Ocean and Atlantic Ocean have revealed that picophytoplankton can account for approximately 60−80% of the total primary produc-tivity (Campbell et al 1997, Grob et al 2011.…”
Section: Introductionmentioning
confidence: 99%